Moisture content and agricultural implement weight effect on soil compaction with depth - Ebreesum, H .K. (Journal of Kerbala for Agricultural Sciences, 2014)
Afield experiment was conducted to determine the compaction resulted in clay loam soil in terms of , bulk density , penetration resistance and saturated hydraulic conductivity at soil depths, (0-10, 10-20 , and 20-30 cm) under the effect of gravimatric moisture contents, (23.05 , 20.57 and 18.57%) and three agricultural implements defferent with type , equipping and total weight (tare + input) , hanging fertilizer spreader (300) kg , fogger (1290) kg and transport wagon (3600) kg . The last two implements as a towed with one axle . Each of above implements represent a compaction load. Compaction treatments were corried out using a wheeled tractor of 2750 kg , run once with each of implement behind it at all moisture contents , in addition to non tracked treatment (control) . The towed implement wheels were positioned to follow tractor wheels . All determination were taken beneath the track center line . The results show that a great compaction occurred within 0-30cm soil depth , due to transport wagon at 23.05% moisture content ,bulk density and saturated hydraulic conductivity values were 1.56 Mg.m-3 and 4.04 mm.h-1 respectively. Exception control treatment, a lower compaction at the same depth above occurred under influence off fertilizer spreader at 18.57% water content, the values of the two soil properties mentioned above (1.39 Mg . m-3 and 36.36 mm.h-1 respectively). The soil within 20-30cm depth was affected significantly by compaction of all implements and moisture content treatments exception fogger and fertilizer spreader at 18.57% moisture content treatments .A higher penetration resistance(2127kPa) was found at soil within 0-30cm depth under influence of transport wagon at 18.57% moisture content.